ANALISIS RISIKO PADA USAHA PENANGKAPAN KEPITING BAKAU DI KECAMATAN SUNGAI KUNYIT KABUPATEN PONTIANAK - Imelda, Imelda (Jurnal Social Economic of Agriculture, 2012)
The aims of this research was : (1) to determine the level ofincome on crab fishing activities, (2) to determine the risk of cost, the riskof production, and the risk of income from crab fishing activities. Researcharea was determined by purposive in sub district Sungai Kunyit with theconsideration that sub district of Sungai Kunyit as the center of fisheriessector in West Borneo Province and most of the people work as afisherman. Analysis that implemented in this research was cost and incomeanalysis and coefficient of variation analysis (CV).The results show that the crab fishing activities in Mendalokvillage sub distric of Sungai Kunyit is profitable for the fisherman withlevel of income is Rp. 9.531.357,-/year. The risk of cost in crab fishingactivities caused by the variance of fixed cost and variable cost. Ther riskof production in crab fishing activities caused by the variance of catchcrabs, the limited of facilites and capital. The risk of income caused by thevariance of catch crabs and the difference of selling price in the in the levelof traders (retailers, traders and wholesalers.Key words : analysis of risk, crab fishing activities, income.